Pendampingan Penguatan Umkm Berbasis Digital Marketing Di Karangmalang Sragen - Nurdyastuti, Tri; Mulyadi, Mulyadi; Sapariyah, Rina Ani; Susila, Linda Nur; Santosa, Jarot; Suroto, Suroto (STIE AUB Surakarta, 2024)
Industrial development is currently in the industrial revolution 4.0 phase, marked by rapid developments in the world of information technology. . The obstacles faced by MSMEs in developing businesses using IT, namely the development of technology and the large number of technology-based products, cause MSMEs to feel confused in determining the appropriate product to be a solution to the problems they face. Not all MSME players in Karangmalang market their products in available market places, such as Shopee, Lazada and Tokopedia. This is because they don't know how to start marketing products through that market place. In digital marketing practices using the Shopee application, MSMEs are provided with how to use the Shopee application, starting from registering, creating an account, uploading products and providing certain tips so that consumers can find our products at the top by optimizing hashtags, uploading them in the feed and providing education to consumers regarding our product. The results of the service can also provide education about the use of technology in digital marketing and it can be concluded that there is an increase in participants' understanding.